WAHBAH ZUHAILIY A SCHOLAR INTERPRETATION IN TWENTY CENTURY - Abd Wahid (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
This essay reveal about a scholar who is steady to science for islamic advancement, trying to spread his message through a variety of writings throughout the world, he is Wahbah Zuhailiy, a Syrian scholar. Even if he is a scholar of Shariah experts, and having a lot of writing about fiqh, but he is also an expert interpretation, it is proved by there are three books of commentary written by him, one of the famous books is al-Tafsir Munir, through this book revealed the intention verses of the Qur’an more clearly. In interpreting the verse, he used methods maudhu’i, besides used Tahlili. Whilethe pattern, he tend to used Adabi Ijma’i and faqhi pattern. Although there are many praising to this interpretation, it still has many weakness, it is obviously what Wahbah Zuhailiy has put itself on the level of scholars interpretation of this century